2000
DOI: 10.1093/emboj/19.21.5884
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus vector silencing is de novo methylase independent and marked by a repressive histone code

Abstract: Retrovirus vectors are de novo methylated and transcriptionally silent in mammalian stem cells. Here, we identify epigenetic modifications that mark retrovirus-silenced transgenes. We show that murine stem cell virus (MSCV) and human immunodeficiency virus type 1 (HIV-1) vectors dominantly silence a linked locus control region (LCR) beta-globin reporter gene in transgenic mice. MSCV silencing blocks LCR hypersensitive site formation, and silent transgene chromatin is marked differentially by a histone code com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
118
2
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 49 publications
14
118
2
3
Order By: Relevance
“…It has also been suggested that retroviral silencing may act through methylation-independent mechanisms, and methylation is only a secondary step in this pathway. [16][17][18][19] Consistent with this, retroviral silencing was reported in mouse embryonic stem cells that are de novo methyltransferase (dnmt3a and dnmt3b) null. 16,20 Up until now, when a UIGD technique is used, the only way to confirm whether embryos or adult mice have received the transgene has been to analyze brains taken from killed animals.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It has also been suggested that retroviral silencing may act through methylation-independent mechanisms, and methylation is only a secondary step in this pathway. [16][17][18][19] Consistent with this, retroviral silencing was reported in mouse embryonic stem cells that are de novo methyltransferase (dnmt3a and dnmt3b) null. 16,20 Up until now, when a UIGD technique is used, the only way to confirm whether embryos or adult mice have received the transgene has been to analyze brains taken from killed animals.…”
Section: Discussionsupporting
confidence: 69%
“…[16][17][18][19] Consistent with this, retroviral silencing was reported in mouse embryonic stem cells that are de novo methyltransferase (dnmt3a and dnmt3b) null. 16,20 Up until now, when a UIGD technique is used, the only way to confirm whether embryos or adult mice have received the transgene has been to analyze brains taken from killed animals. In order to construct adult mouse models using the UIGD technique, therefore, gene-transferred mice should be discriminated against other littermates without killing.…”
Section: Discussionsupporting
confidence: 69%
“…2,5,6 Especially, acetylation status of lysine residues within histone tails are generally accepted as markers of chromatin activation. 27 For this purpose, we performed ChIP assay to detect histone acetylation levels of proviral ArsI and CMV promoter ( Figure 7).…”
Section: Effect Of Arsi On Histone Acetylationmentioning
confidence: 99%
“…The mechanism of transgene silencing remains to be elucidated; however, accumulating evidence suggest that epigenetic alterations of the transgene, such as DNA methylation and/or histone modifications, are likely components. 3,5,6 Engineering retroviral vectors to avoid epigenetic alterations is needed for successful application of gene therapy. Retroviral vectors currently in experimental and/or clinical practice are categorized into two groups: oncoretrovirus-based (eg Moloney-murine leukemia virus, MoMLV) and lentivirus-based (eg human immunodeficiency virus type-1, HIV-1) vectors.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Another report described a methylase-independent mechanism of proviral silencing through MoMuLV and immunodeficiency virus type 1 (HIV-1) cis-acting sequences. 30 Facing this problem we decided to transduce the CD34 + progenitor cells with titers ranging from 100 to 150 MOI, which resulted in a high tyrosinase mRNA and concomitant EGFP expression in the first 3 days after transduction. Nevertheless, we revealed a strong silencing of transgenes in the cells during the expansion phase of the progenitor cells.…”
Section: Discussionmentioning
confidence: 99%